Health outcomes among HIV‐positive Latinos initiating antiretroviral therapy in North America versus Central and South America. Issue 1 (18th March 2016) - Cesar, Carina; Koethe, John R; Giganti, Mark J; Rebeiro, Peter; Althoff, Keri N; Napravnik, Sonia; Mayor, Angel; Grinsztejn, Beatriz; Wolff, Marcelo; Padgett, Denis; Sierra‐Madero, Juan; Gotuzzo, Eduardo; et al.
Abstract : Introduction: Latinos living with HIV in the Americas share a common ethnic and cultural heritage. In North America, Latinos have a relatively high rate of new HIV infections but lower rates of engagement at all stages of the care continuum, whereas in Latin America antiretroviral therapy (ART) services continue to expand to meet treatment needs. In this analysis, we compare HIV treatment outcomes between Latinos receiving ART in North America versus Latin America. Methods: HIV‐positive adults initiating ART at Caribbean, Central and South America Network for HIV (CCASAnet) sites were compared to Latino patients (based on country of origin or ethnic identity) starting treatment at North American AIDS Cohort Collaboration on Research and Design (NA‐ACCORD) sites in the United States and Canada between 2000 and 2011. Cox proportional hazards models compared mortality, treatment interruption, antiretroviral regimen change, virologic failure and loss to follow‐up between cohorts. Results: The study included 8400 CCASAnet and 2786 NA‐ACCORD patients initiating ART. CCASAnet patients were younger (median 35 vs. 37 years), more likely to be female (27% vs. 20%) and had lower nadir CD4 count (median 148 vs. 195 cells/µL, p <0.001 for all). In multivariable analyses, CCASAnet patients had a higher risk of mortality after ART initiation (adjusted hazard ratio (AHR) 1.61; 95% confidence interval (CI): 1.32 to 1.96), particularly during the first year, but a lower hazard of treatment interruption (AHR: 0.46; 95% CI: 0.42 to 0.50), change to second‐line ART (AHR: 0.56; 95% CI: 0.51 to 0.62) and virologic failure (AHR: 0.52; 95% CI: 0.48 to 0.57). Conclusions: HIV‐positive Latinos initiating ART in Latin America have greater continuity of treatment but are at higher risk of death than Latinos in North America. Factors underlying these differences, such as HIV testing, linkage and access to care, warrant further investigation.